Pengaruh Latihan Skipping dan Naik Turun Tangga Terhadap Tinggi Loncatan Pada Atlit Bola Voli Klub Tunas Kabupaten Tegal (Universitas Negeri Semarang, 2022)
The purpose of this study was to determine the effect of skipping exercises and going up and down stairs on the vertical jump height of volleyball athletes at Tunas Tegal Club. The method used in this study is experimental, with a